Pengaruh Persaingan Jam Kerja dan Kebijakan Tarif pada Ojek Online terhadap Tingkat Pendapatan Mitra Driver Goride di Kota Denpasar - Marthen Rohi Riwu; Ni Made Yudhaningsih; Putu Budhiyasa (PT. PENERBIT TIGA MUTIARA, 2025)
The rapid growth of the online transportation sector in Indonesia has driven a significant transformation in urban mobility systems, including in Denpasar City. One of the impacts of this development is the increasing competition among driver-partners, which directly affects fluctuations in their income. This study aims to empirically analyze the influence of competition level, working hours duration, and fare policies on the income of GoRide partners in Denpasar City. A quantitative approach was used in this research, with the population consisting of all active GoRide driver-partners in the area. The sample was determined using the Slovin formula with a 10% significance level, resulting in 67 randomly selected respondents. Data were collected through the distribution of structured questionnaires and analyzed using multiple linear regression methods to examine the effect of each independent variable on income as the dependent variable. The results show that the competition variable has a significant negative effect on partner income, indicating that the higher the level of competition, the lower the income earned. Conversely, working hours have a positive and significant effect, indicating that increased working duration directly contributes to higher income. Meanwhile, fare policy shows a positive but insignificant effect, meaning that although there is a statistically positive relationship, the effect is not strong enough to significantly impact income. These findings highlight the importance of efficient management of working hours and strategic adaptation to competition levels as efforts to maintain the economic sustainability of driver-partners. In addition, platform providers are advised to periodically review fare policies to ensure they remain aligned with market dynamics and partner needs, in order to maintain a sustainable income balance.